Penyuluhan Kesehatan tentang Pentingnya Imunisasi pada Anak di Wilayah Kerja Puskesmas Alas Kabupaten Sumbawa - Herni Hasifah; Nur Arifatus Sholihah (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
Immunization is something that must be given to children. Immunization services can be obtained in government-owned health service units, such as hospitals, puskesmas and even posyandu spread throughout the country. Immunization is an attempt to provide protection against diseases that can lead to disability and death. So Indonesian children, who are the next generation of the nation, must get complete immunization. However, the Word Health Organization (WHO) states that 1 in 5 children in the world are recorded as having not received routine immunizations. The 2021 routine immunization report showed a decrease in complete basic immunization coverage by 9.5% from 93.7% (2019) to 84.2% (2021), as well as a decrease in measles-rubella baduta coverage by 14.2% from 72.7% (2019) to 65.3% (2020). Then there was a decrease in measles-rubella baduta coverage by 6.8% from 65.3% (2020) to 58.5% (2021). The impact of the decrease in coverage is that an increase in the number of children whose immunization status is incomplete has resulted in an increase in the number of PD3I cases and the occurrence of Extraordinary Events (KLB PD3I) such as measles, rubella and diphtheria in several regions (BIAN, 2022). This service will be held in November 2022 at the Posyandu Desa Luar working area of the Alas Health Center. This community service activity is carried out by an extension method accompanied by giving posters to the participants of the activity. In its implementation, this activity is assisted by posyandu cadres and midwives in the Alas Health Center work area. Participants were very enthusiastic about participating in the activity as evidenced by the active participants in the discussion / question and answer session.